Unraveling The Shields And Swords: The Duel Of Innate And Adaptive Immunity Against Filarial Invaders - Brahmana, Ririn Efranisa Sembiring; Firmansyah, Yohanes (Universitas Pahlawan Tuanku Tambusai, 2024)
The immune system, comprising innate and adaptive components, is crucial for defending the human body against various infectious agents, including filarial parasites. Filariasis, caused by thread-like nematodes, poses a significant health risk in tropical and subtropical regions, affecting over 120 million people worldwide. Understanding the immune response to filarial infection is essential for developing effective treatments and preventive strategies. A comprehensive literature review was conducted, focusing on the human immune response to filarial infections, particularly the roles of the adaptive and innate immune systems. Systematic searches of databases such as PubMed, Scopus, Web of Science, and Google Scholar were carried out, with search terms including